(3GdaVjdI (B:s (3QhGjI (B/s - (3GdCYQL, hGSjfjs; (3GdefadhWjs ((3GdLRGFQ (B:s (3ehae ddfTQh GdJhRjY (B;(3GdeDSSI GdhWfjI ddafhf GdeWHYjI ,s, 1989)
(3deGPG QhGjI GdaVjdI GdGf gfGc LhGfH eJYOOI JYQVgG eKd gPg GdGSFdI bHd GdONhdaj eMGhdI GdGbJQGH Gdi LhGfH eG bO jchf ebfYG fbGT cKjQ OGQh eGjRGd jOhQ MJi GdGf Mhd GTcGdjI GdfgVI GdJj dG jecf de jcf eecfG GHOG Gf JHfj NGQL GdGNHG GdKbGaj h GdMVGQj GdeTQhW HOhQg h HTcd JGQjNj GdYdGJ GdNdGaI eY GdKbGaGJ GdGfSGfjI GdGNQi YUQ GdJfhjQ GdKbGaj GdYQHj GdPj de jJHdhQ HTcd aGYd cGfhGbYG Hjf MOjf aGYdjf GeG GdKGQ ef ehbY GdGSJdGH Gh GdJCKQ ef ehbY GNQ GcKQ GbJfGYG GSgGeG aj GdJWhjQ GdKbGaj GdYQHj eKdeG MOK HGdfSHI ddadSaI GdYQHjI GdESdGejI GdJj cGf GHf QTO NdGUJgG GdYdejI GdQGbHIs
Keywords: (3GdaVjdIs; (3QhGjI s